The effect of pressure of environmental business and NGO interests on the policy of restricting the EU palm oil import from Indonesia and Malaysia - Triwardani Sopiana Henny (EDP Sciences, 2021)
This research will explain how the pressure originating from the interests of business and environmental NGOs in the European Union on the policy of limiting the import of palm oil from Indonesia and Malaysia. As we know, Indonesia and Malaysia are the largest palm oil producing countries in the world and export a lot of their palm oil to the European Union. Recently, the European Union has issued a policy of limiting the import of palm oil for biodiesel products, which policy has been in effect in June 2019. In this policy Limitation of the use of palm oil throughout 2021-2023 will be at the same level in 2019, then its use will be reduced gradually until it runs out in 2030. Business interests and environmental NGOs here have a strong enough influence in the issuance of the policy. This study uses the concept of a Bureaucratic Political Model to answer how pressures from business interests and environmental NGOs influence the policy of import restrictions on palm oil for biodiesel products in the European Union.